Safety culture in the primary health care settings based on workers with a leadership role: the psychometric properties of the Slovenian-language version of the safety attitudes questionnaire - short form - Zalika Klemenc-Ketis; Irena Makivić; Antonija Poplas-Susič (BMC, 2018)
Abstract Background Safety culture describes leader and staff interactions, attitudes, routines, awareness, and practices within an organisation. With this study, we aimed to determine the psychometric properties of the Slovenian-language version of the Safety Attitudes Questionnaire (SAQ) - Short Form in primary health care settings. Methods This was a cross-sectional study in the largest primary health care in Slovenia. We invited all employees with a leadership role to participate in the study (N = 211). We used the Slovenian-language version of the SAQ - Short Form. Results There were 154 participants in the final sample (73.0% response rate), of which 136 (88.3%) were women. The mean age of the sample was 46.2 ± 10.0 years. Exploratory factor analysis put forward six factors: 1) Perceptions of Management; 2) Stress recognition; 3) Teamwork Climate; 4) Communication; 5) Safety Climate; 6) Working Conditions and Satisfaction. This model explained 61.7% of the variance of the safety culture in the primary health care setting. The reliability of the whole scale and of the six factors, assessed using Cronbach's alpha, was all above 0.78. Conclusion The results of our study suggests that the Slovenian-language version of the SAQ - Short Form with six factors could be a reliable and valid tool for measuring the safety culture in the primary health care workers with leadership role In Slovenia. The Slovenian version differed from the original SAQ - Short Form and the majority of other translated versions. Also, the data was from one health centre only and therefore we cannot draw strong conclusions on its external validity.